Identification of two novel type II topoisomerase mutations in Enterococcus spp. isolated from a hospital in China - Su, Rina; Peng, Yunzhi; Wang, Zhanli; Yu, Hui; Wu, Qi (Archives of Biological Sciences, 2021)
Paper description: The mutational status of type II topoisomerases and the relationship of mutations with quinolone resistance is incompletely understood. DNA sequencing was performed to investigate the mutational status of the quinolone resistance-determining regions of type II topoisomerases in clinical isolates of enterococci. Two novel substitutions of faecalis were identified. Three-dimensional modeling revealed that these novel amino acid substitutions disrupt the water/metal-ion bridge and decrease the interaction between enzymes and ciprofloxacin. These results elucidate the mechanisms of type II topoisomerase-mediated quinolone resistance in clinical isolates of enterococci. Abstract: Type II topoisomerases, including DNA gyrase (GyrA) and topoisomerase IV (ParC), contribute to fluoroquinolone resistance in Enterococcus spp. This study investigated the mutational status of the quinolone resistance-determining regions (QRDRs) of GyrA and ParC in the clinical isolates of enterococci from a hospital in Baotou, China. We analyzed 110 enterococcal isolates, including 57 Enterococcus faecalis and 53 Enterococcus faecalis faecium. The resistance rates of E. faecalis and E. faecium to ciprofloxacin were 63.16% and 84.91%, respectively. We found that 32 samples of E. faecalis and 42 of E. faecium had single or combined mutations in gyrA and/or parC, which were all resistant to ciprofloxacin. Only two ciprofloxacin-resistant E. faecalis isolates had no mutation. No mutations in gyrA and parC genes in all ciprofloxacin-susceptible isolates were found. Ciprofloxacin minimal inhibitory concentrations (MICs) in the mutation group were significantly higher than those of the non-mutation group, indicating that mutations in the QRDRs of gyrA and parC were correlated with MIC elevation. Two novel substitutions (GyrA Ser83Phe and ParC Ser80Leu) of E. faecalis were identified herein. Three-dimensional modeling revealed that these novel amino acid substitutions could disrupt the water/metal-ion bridge and decrease the interaction between the enzymes and ciprofloxacin. The data showed a diversity of mutation types in QRDRs of type II topoisomerases whose association with fluoroquinolone resistance in clinical isolates of enterococci warrants further investigation.